2021
DOI: 10.1038/s41598-021-93077-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel use of social media to assess and improve coastal flood forecasts and hazard alerts

Abstract: Coastal communities and infrastructure need protection from flooding and wave overtopping events. Assessment of hazard prediction methods, used in sea defence design, defence performance inspections and forecasting services, requires observations at the land-sea interface but these are rarely collected. Here we show how a database of hindcast overtopping events, and the conditions that cause them, can be built using qualitative overtopping information obtained from social media. We develop a database for a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…However, the distribution of this critical foreshore width suggests that the 200 m in front of the structure mostly influences wave overtopping at Crosby, with the first 30 m being the most critical-with tan(m) = 1:10 (or cot(m) = 10). This finding supports the conclusion of Brown et al (2021) who found that the height of the beach within about 10 m of the structure toe had a strong influence on wave overtopping for any given wave and water level conditions. As the first 200 m in front of the structure is also the most dynamic (Fig.…”
Section: Critical Foreshore Width For Wave Overtopping At Crosbysupporting
confidence: 91%
See 3 more Smart Citations
“…However, the distribution of this critical foreshore width suggests that the 200 m in front of the structure mostly influences wave overtopping at Crosby, with the first 30 m being the most critical-with tan(m) = 1:10 (or cot(m) = 10). This finding supports the conclusion of Brown et al (2021) who found that the height of the beach within about 10 m of the structure toe had a strong influence on wave overtopping for any given wave and water level conditions. As the first 200 m in front of the structure is also the most dynamic (Fig.…”
Section: Critical Foreshore Width For Wave Overtopping At Crosbysupporting
confidence: 91%
“…In December 2013, an open-access community Facebook page was established for Crosby with the title, "I'm at Crosby beach and the weather is …" (Facebook Page) and community members were able to report when wave overtopping of any magnitude occurred (Brown et al, 2021). Using the photographs from the page (Fig.…”
Section: Social Media Reportsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional ume studies are also often focussed on extreme conditions 20 , making the predictions from current numerical tools even more uncertain for the more frequently occurring, less energetic ("nuisance") type of overtopping that can nevertheless pose a hazard to pedestrians 21 , as well as contributing to ood events. Currently the uncertainties in the overtopping predictions for extreme conditions are estimated as a factor of 3, but for more frequently occurring conditions, and/or less common sea wall structures, these uncertainties rise to orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%